1980
DOI: 10.1002/ajmg.1320050403
|View full text |Cite
|
Sign up to set email alerts
|

The ring nature of a tiny supernumerary chromosome fragment

Abstract: We report a 5 1/2-year-old girl with a tiny supernumerary chromosome fragment found in mosaic. The ring nature of the tiny fragment was demonstrated by the detection of the characteristic products of a ring chromosome. The clinical consequence of a ring chromosome and the impact of finding a supernumerary chromosome fragment, especially in the practice of prenatal chromosome diagnosis, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A good prognosis in conjunction with a small supernumerary chromosome of 1, 9, or 16 origin was reported in three cases by Callen et al [1990] in which supernumerary ring chromosomes with large amounts of heterochromatin were interpreted as not clinically active. However, the two cases reported by Hoo et al [1974, 1980], which showed heterochromatic regions within the small ring chromosomes, were considered accountable in the presentation of mild mental retardation, although a chance association cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…A good prognosis in conjunction with a small supernumerary chromosome of 1, 9, or 16 origin was reported in three cases by Callen et al [1990] in which supernumerary ring chromosomes with large amounts of heterochromatin were interpreted as not clinically active. However, the two cases reported by Hoo et al [1974, 1980], which showed heterochromatic regions within the small ring chromosomes, were considered accountable in the presentation of mild mental retardation, although a chance association cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these characteristics are present in our patient, whose cytogenetic situation also shows a remarkable stability. Considering her age of nearly 30 years, there seems to have been very little tendency to the euploidization, observed in other cases [Hoo et al, 1980;Benn and Hsu, 19841. The hypothesis of the rings is also supported by the likely exclusion that the supernumerary chromosomes are small bisatellited markers.…”
Section: Djscussjonmentioning
confidence: 99%
“…Occasionally, the accessory chromosomes have been identified as rings [Hoo et al, 1974a[Hoo et al, , 1980Ventruto et al, 1977;Kaffe et al, 1977;Zamboni et al, 1980;Fryns et al, 354 Tozzietal. 198 1, 198% Copeland et al, 19851. As to their clinical significance, the statement can be made that, in general, presence of euchromatin in the mar and de novo appearance in the proband are accompanied by mental retardation, whereas heterochromatic, inherited mar's are in most cases associated with a normal phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Ring chromosomes have long been recognized in classical cytogenetics on the basis of their shape and properties (Hoo et al 1980). A ring chromosome can lead to clinical symptoms due to partial deletion (mohosomy) of that certain chromosome.…”
mentioning
confidence: 99%